The Influence of Environmental, Social, and Governance (ESG) Scores on Stock Returns Using Firm Size as a Control Variable: A Case Study of LQ45-Indexed Companies Listed on the Indonesia Stock Exchange (2019–2023) - Nabilah Putri Nasrina; Khairunnisa Khairunnisa (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) scores on stock returns, incorporating firm size as a control variable. The research focuses on companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. A total of 18 companies were selected through purposive sampling, yielding 90 panel data observations. This study employs a quantitative approach with an explanatory research design. Descriptive statistics and panel data regression analyses were conducted using the EViews application to assess both the individual (partial) and joint (simultaneous) effects of ESG dimensions on stock returns. The findings reveal that the Environmental and Governance scores significantly and positively affect stock returns, indicating that companies with higher environmental responsibility and stronger governance mechanisms tend to deliver better stock performance. In contrast, the Social score does not exhibit a statistically significant effect on stock returns, suggesting that social initiatives are yet to be perceived as a major investment consideration in the Indonesian capital market. The control variable, firm size, was included to account for the effect of company scale on stock performance. Overall, the results support the signaling theory, which posits that ESG disclosures serve as credible signals to investors.